2002
DOI: 10.1126/science.1075857
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale, Decelerating, Relativistic X-ray Jets from the Microquasar XTE J1550-564

Abstract: We have discovered at x-ray and radio wavelengths large-scale moving jets from the microquasar XTE J1550−564. Plasma ejected from near the black hole traveled at relativistic velocities for at least four years. We present direct evidence for gradual deceleration in a relativistic jet. The broadband spectrum of the jets is consistent with synchrotron emission from high energy (up to 10 TeV) particles accelerated in shock waves formed within the relativistic ejecta or by the interaction of the jets with the inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
264
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(279 citation statements)
references
References 28 publications
12
264
2
1
Order By: Relevance
“…However, very long baseline interferometric observations of the neutron-star binary Sco X-1 [12,13] have revealed knots with mildly relativistic bulk velocities (β ∼ 0.5) which are energised by a beam which is itself not directly detectable, but must have a Lorentz factor Γ > 3. Furthermore, it has been suggested that the observed synchrotron emission results from a moving shock [14] (as discussed for AGN and Gamma-ray bursts), a possibility supported by recent observations of large-scale X-ray jets from a transient black hole X-ray binary, revealing in-situ acceleration of electrons to TeV energies [15].…”
mentioning
confidence: 87%
“…However, very long baseline interferometric observations of the neutron-star binary Sco X-1 [12,13] have revealed knots with mildly relativistic bulk velocities (β ∼ 0.5) which are energised by a beam which is itself not directly detectable, but must have a Lorentz factor Γ > 3. Furthermore, it has been suggested that the observed synchrotron emission results from a moving shock [14] (as discussed for AGN and Gamma-ray bursts), a possibility supported by recent observations of large-scale X-ray jets from a transient black hole X-ray binary, revealing in-situ acceleration of electrons to TeV energies [15].…”
mentioning
confidence: 87%
“…Jet breaks have been isolated in almost a dozen hard state systems (e.g., Corbel et al 2002;Russell et al 2013). However, we caution that drawing a physical connection between a jet break for J1357.2 in quiescence and for the hard state systems is currently premature, as the jet breaks that have been isolated in hard state systems are intimately related to the location along the jet where (some fraction of) particles are accelerated into non-thermal distributions (e.g., Polko, Meier & Markoff 2013.…”
Section: A Synchrotron Origin For Quiescent Bhxb Emissionmentioning
confidence: 99%
“…The non-detection suggests either a sub-TeV cut-off in the electron energy distribution and/or a magnetic field strength closer to the equipartition value. A detection in X-rays of the discrete ejecta would imply TeV electron energies, as in XTE J1550-564 and H1743-322 (Corbel et al 2002(Corbel et al , 2005. The HESS upper limits would then rule out sub-equipartition magnetic fields.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, ejected plasma clouds were detected at distances of 0.1-1 pc from the binary. They showed a power-law spectrum extending from radio to X-rays that was presumably produced by a single electron distribution reaching TeV energies (Corbel et al 2002(Corbel et al , 2005. The highly energetic particles are expected to generate a very faint VHE emission as a result of inverse Compton scattering of ambient radiation fields.…”
Section: Introductionmentioning
confidence: 99%